Motion – All Patients with GERD Should Be Offered Once in a Lifetime Endoscopy: Arguments for the Motion - David Armstrong (Canadian Journal of Gastroenterology)
Proton pump inhibitor therapy is so successful at relieving refluxrelated symptoms and healing esophageal erosions that it has supplanted formal diagnostic techniques, such as endoscopy and esophageal pH monitoring, for the initial management of gastroesophageal reflux disease. The response to antisecretory therapy is not indicative, however, of Barrett’s esophagus or esophageal adenocarcinoma. Patients with prolonged and severe reflux symptoms, especially if they are over the age of 60 years, are at risk of these complications. For them, endoscopy is the only appropriate investigation for detecting Barrett’s esophagus and dysplasia or cancer. Because of the difficulty in distinguishing dysplasia from inflammatory and regenerative changes, endoscopy should be undertaken while the patient is on effective antisecretory therapy. Endoscopy should be offered only to patients who are suitable for further therapy (especially esophagectomy), and only if they understand the implications of abnormal findings. The published evidence suggests that the application of clear guidelines would not overwhelm health care resources, and that fewer than 20% of patients with Barrett’s esophagus would eventually undergo endoscopic surveillance.